Early career experiences of navigating journal article publication: Lessons learned using an autoethnographic approach - Merga, Margaret; Mason, S.; Morris, J. (2018)
© 2018 The Author(s). Learned Publishing © 2018 ALPSP. The successful publication of peer reviewed academic journal articles is an essential achievement for early career researchers (ECRs) seeking to establish themselves in their profession. However, this journey can pose several significant challenges for ECRs. We use an autoethnographic approach that draws deeply on our lived experience as ECRs to capture our recent and current experiences of negotiating the academic journal article publication journey to explore the tensions, contradictions, and benefits encountered in the journey. We critically examine challenges we experienced in choosing a target journal and negotiating the follow-up process; undertaking revisions; and our experiences of limitations and possibilities in peer review and editorial support. While the peer review journal writing process has played a significant role in supporting us to become more effective ECRs, we also highlight challenges we faced negotiating ethical quandaries in this space, as well as illustrate how our preconceptions of a simple publication journey were confounded by subsequent experience of the complex realities of the space. We also suggest that educational interventions are indicated to provide ECRs support in foundational knowledge about what constitutes valuable revisions, an effective paper, and the scope of issues that can be addressed to make a paper more effective, with reference to the possibility of academic mentoring to support this need. Finally, we explore our findings in light of the tensions imposed by the relative inexperience and lack of power yielded by ECRs.